Analisis Perlindungan Konsumen Terkait Produk Komputer Rakitan - Hanapi, Yayan (Gorontalo Law Review, 2018)
The effectiveness of Article 25 Consumer protection law among business actors in this case the assembled computer seller shop is still not effective because apparently there are assembled computer seller stores that do not understand about the importance of after sales service. In connection with the Implementation of the Consumer Protection Law, particularly Article 25, it is necessary to socialize by the Department of Industry and Trade because of the importance of after sales service for the community as the consumer and the seller or as the producer so that Article 25 of Law Number 8 Year 1999 concerning consumer protection can implemented accordingly. The process of dispute settlement conducted by both parties both consumer and computer assembler sales shop is to take the non litigation path without going through BPSK.